Arsênio em amostras de sedimento da microbacia do Ribeirão Guamium, Piracicaba, SP e seu efeito em organismos zooplanctônicos - Ohashi, Thaís Luri (2010)
Arsenic is an essential chemical element for life, although it can be extremely toxic at concentrations slightly above those required for living organisms. In Brazil, generally well-standardized internationally test organisms are used in Aquatic Toxicology. Although sensitive, it does not occur in Brazilian ecosystems, increasing the difficulties on assessing the impacts of chemicals on specific niches of the local biota. Furthermore, the toxicity test using exotic species, do not match the tropical and subtropical ecosystems abiotic conditions, which have different characteristics such as conductivity, hardness and temperature, among other variables that modify the response of test organisms and even the own toxicity of the chemical agent. Thus, ecotoxicological assays are of utmost importance when using native species, in order to assess it sensitivity to several toxic agents. The present study was proposed to assess for the toxicity of Guamium River bottom sediment, Piracicaba hydrographic basin, São Paulo, by using test organisms such as Paramecium caudatum protozoan Ehrenberg, 1833 and Ceriodaphnia silvestrii cladocera Daday, 1902. To reach for these goals two sampling campaigns were carried out, one in the dry season and another during the rainy season, in 9 points through the entire length of the river main channel, to verify spatial variation as a function of different surrounded land use. Sediment samples were analyzed for total and available As, As3+ and As5+, relating the obtained data with acute toxicity bioassays results for inorganic As species. Taking into account the modification of As oxidation state by the sample preparation conditions, in the rainy season, analytical results were compared to those predict by the pH x Eh stability diagram. Total and inorganic As species were also determinate in the Certificated Reference Material WQB-1. The acute toxicity of As3+ and As5+ solutions were evaluated for zooplankton, by using the same test organisms, quantifying the absorption/adsorption of the semi-metal in the experiments organisms. Chemical analysis of sediment samples resulted in toxic levels concentrations of total As, As3+ and As5+, especially in the Points of the River s Source (P0), Tanquinho s District (P1) and Dial Animals (P5) of Guamium River, confirming with the points at which the supernatant had higher concentrations of total As. The results obtained from the sediment analysis were similar to the theoretical values provided using the pH x Eh stability diagram, which indicated prevalence of As5+. The method of determining total As presented analytical precision when it was compared to the Certificated Reference Material WQB-1, which like the samples, presented different fractions of As in its inorganic form. According expected by the literature, the reduced form (As3+) was more toxic than the oxidized form (As5+), and C. silvestrii is more sensitive to arsenic and sediment samples than the P. caudatum. By spectrometry of atomic absorption technique with electrothermal atomization in graphite furnace (GFAAS) it was determinated As levels in the surviving organisms and in the case, the dead of the highest concentration used. In protozoan, the bioaccumulated levels ranged from 29,8 to 70,0 pg x individual As3+ or 10,5 to 17,5 μg x g-1 of dry weight (dw) As3+ and from 183,0 to 282,6 pg x individual As5+ or 45,8 to 70,7 μg x g-1 dw As5+. In cladocera, the levels ranged from 75,9 to 149,3 pg x individual As3+ or 22,4 to 44,1 μg x g-1 dw As3+ and from 1.575,4 to 1.630,2 pg x individual As5+ or 465,2 to 481,4 μg x g-1 dw As5+. Even considering both, the tested organisms small size and the low concentrations used, it was possible to associate with As, bioaccumulating this semi-metal and, thus, has an important role in the bioavailability of this along the food chain.